Improving Student Balinese Language Learning Outcomes through Interactive Animated Video Based on a Contextual Method - Ni Putu Listya Devi; I Komang Sudarma (Universitas Pendidikan Ganesha, 2023)
The Balinese language's position as a mother tongue or regional language contributes to establishing the identity of its people. However, the use of Balinese is decreasing over time, and the quantity of speakers is decreasing. This study aims to develop interactive animated video media based on contextual method to improve students’ Balinese Language learning outcomes. Hannafin and Peck's model which comprises three processes (needs analysis, design, development, and execution) was employed in this development study project. The information was gathered using tests, questionnaires, observations, documentaries, and surveys. Data analysis techniques include the t-test, inferential statistical analysis, and quantitative descriptive analysis. Three students participated in the solo trials, nine in the small group trials, and sixteen in the outdoor tests of this study. Experts in learning media, design, and content served as the subjects. The results of the individual trial, small group trial, field trial, learning content expert test, learning design expert test, learning media expert test, and the learning media expert test were all excellent, with percentage scores of 96.66%, 94.66%, 90.22%, and 98.125%, were used to determine the validity of the interactive animated video media. The t-test illustrates the effectiveness of interactive animated video media by showing significant variations in student learning outcomes between the pre-and post-use media. Since the post-test results of the children are above the National Minimum Completeness Criteria, it is clear that interactive animated video media is an effective tool to assist Balinese Language learning process.